2015
DOI: 10.1177/1073191114568301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Measurement Invariance Between Parents Using the Strengths and Difficulties Questionnaire (SDQ)

Abstract: Parent ratings of their children's behavioral and emotional difficulties are commonly collected via the Strength and Difficulties Questionnaire (SDQ). For the first time, this study addressed the issue of interparent agreement using a measurement invariance approach. Data from 695 English couples (mothers and fathers) who had rated the behavior of their 4.25-year-old child were used. Given the inconsistency of previous results about the SDQ factor structure, alternative measurement models were tested. A five-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 55 publications
(103 reference statements)
3
57
1
Order By: Relevance
“…In contrast, parenting stress experienced by mothers was related to concerns for interpersonal relationships with the people around them such as peer problems, and for the children's internal aspects such as emotional symptoms. Thus, possible explanations for the differences in children's behavioral characteristics related to parenting stress include the following: fathers tending to be more sensitive to and overestimating their children's externalizing and abnormal behaviors and underestimating their strengths in comparison with mothers; mothers tending to be more interested in children's self‐regulation skills including emotional aspects in daily life; the influence of the couple's relationship (if the relationship is strong enough for the parents to share information regarding the child, the differences in the evaluation of the child decreases); children presenting different behavior to the father and mother; the basic attributes of each parent (mental health, employment status, economic status, alcohol misuse, self‐esteem, parenting support conditions) and so on. Therefore, we believe it is necessary to evaluate different forms of support for mothers and fathers when providing parenting support to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, parenting stress experienced by mothers was related to concerns for interpersonal relationships with the people around them such as peer problems, and for the children's internal aspects such as emotional symptoms. Thus, possible explanations for the differences in children's behavioral characteristics related to parenting stress include the following: fathers tending to be more sensitive to and overestimating their children's externalizing and abnormal behaviors and underestimating their strengths in comparison with mothers; mothers tending to be more interested in children's self‐regulation skills including emotional aspects in daily life; the influence of the couple's relationship (if the relationship is strong enough for the parents to share information regarding the child, the differences in the evaluation of the child decreases); children presenting different behavior to the father and mother; the basic attributes of each parent (mental health, employment status, economic status, alcohol misuse, self‐esteem, parenting support conditions) and so on. Therefore, we believe it is necessary to evaluate different forms of support for mothers and fathers when providing parenting support to them.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of a child, however, tends to differ between the mother and father regardless of whether the child has a disability or not, although parents have key information about the child's behavioral characteristics . Van der Veen‐Mulders et al .…”
mentioning
confidence: 99%
“…An aggregated multilevel structural equation model (controlling for preschool effects; Sammons et al, 2013) was used to estimate the impact of early socio-economic risk upon preschool home learning environment and the direct, indirect (via intermediate measures), and total (direct plus indirect) effects of both upon children's reading ability and academic self-concept at ages 7 and 10 years (see Figure 1). Missing data were estimated using the weighted least squares approach (Asparouhov & Muth en, 2010); a technique analogous to using Full Information Maximum Likelihood (Chiorri et al, 2015). All variables were standardized (z-scored) a priori to ease model convergence, and the Weighted Least Squares Means and Variance adjusted estimator was used to mitigate any spurious effects caused by nonnormality (Muth en & Muth en, 2012).…”
Section: Analytic Approachmentioning
confidence: 99%
“…This was boosted through the use of a relatively novel (and particularly accurate) approach to the specification of latent measures (of children's academic self-concept) from ordinal observed predictors. Unlike much past research, we respected the ordinal nature of the four self-concept questions that the original EPPE researchers asked of children rather than (mis)treating them as continuous (for details of this procedure, see Chiorri et al, 2015).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…In all of the above-mentioned studies, ADHD symptoms were assessed with other instruments than the SDQ. In contrast, two studies addressing differences in parent-reported SDQ scores for hyperactivity/inattention in children from a community sample indicate an association in the opposite direction, with higher levels of ADHD symptoms reported by fathers than by mothers (Chiorri, Hall, Casely-Hayford, & Malmberg, 2016;Davé, Nazareth, Senior, & Sherr, 2008). It is not clear yet how these mixed findings should be interpreted, since multiple factors affect how parents perceive, interpret, and report their children's behavior (De Los Reyes & Kazdin, 2005).…”
Section: Discussionmentioning
confidence: 95%